Factorial Validity of the Emotional Verbal Learning Test-Spanish (EVLT-S). (30th August 2019) - Zink, D N; Reyes, E; Kuwabara, H; Strauss, G P; Allen, D N
Abstract: Objective: The EVLT-S is the Spanish translation of a novel measure of emotional verbal learning and memory. The current study aimed to preliminarily examine the factorial validity of the EVLT-S to determine if its latent structure was similar to that identified for the EVLT by Strauss and Allen (2013) in a sample of 329 English speakers. Participants and Method: Two principal component analyses (PCAs) were conducted to examine the latent structure of the EVLT-S. The first PCA examined EVLT/EVLT-S performance in a combined sample of English language-dominant participants (n = 52; Age M = 23.1 years; Education M = 13.4 years; 32.7% White non-Hispanic, 36.5% Hispanic, and 30.8 % other; 55.8% female) and Spanish language-dominant participants (n = 50; Age M = 20.3 years; Education M = 12.8 years; 98% Hispanic and 2% other; 72% female). The second PCA was conducted with the Spanish dominant sample alone (n = 50). PCAs were conducted using comparable scores and procedures reported by Strauss and Allen (2013), including scores for the four emotion categories (happiness, sadness, anger, anxiety), varimax rotation, and Kaiser-Guttman criteria to determine the number of components, allowing for direct comparisons between the current results and those previously reported. Results: Both PCA's identified five components that accounted for 68.6 – 70.4 percent of the variance and attained simple structure. Based on factor loadings, these components were labeled Anger, Sadness, Happiness, Anxiety, and Short-Term Memory (STM). Conclusions: The PCA analyses in this study were exploratory in nature but were remarkably consistent with prior results attained in a much larger sample (n = 329) of English speakers. Results provide preliminary support for a stable and generalizable EVLT latent structure in Spanish and English versions. Future studies with larger samples using confirmatory factor analyses are needed to further establish the factorial validity of the EVLT-S. References: Strauss, G. P., & Allen, D. N. (2013). Emotional Verbal Learning Test: development and psychometric properties.  Archives of clinical neuropsychology,   28 (5), 435-451.